MENGURAI BENANG KUSUT DUALISME NIKAH SIRRI (Upaya Meratifikasi Rancangan Undang-Undang Nikah Sirri) - Suhaeri, Suhaeri (Sunan Kalijaga State Islamic University & The Asia Foundation, 2013)
The emergence of the Draft Bill on the Religious Judiciary Material Law on Marriage -otherwise known with the Draft Bill on Sirri Marriage- has brought a lengthy polemic debate. This issue essentially rests on a legal matter, the duality of Sirri marriages; which are legal according to Islamic law but illegal according to formal law (national civil law). This led many actors to disregard the need for the ratification of the Draft Bill, where in fact the Draft Bill’s ratification intends to uphold justice. This shows that there is a faulty perception by society in understanding Islamic law’s position on Sirri marriages. Therefore, this article will attempt to rectify society’s understanding on Sirri marriage through the fiqh approach. The conclusion which may be drawn are that Sirri marriages contain two harms (kemafsadatan) at the same time (adultery and harming others). According to fiqh, when a choice exists between two harms, the avoidance of the greater should be chosen. In this case, the greater harm comes from harming wives and children in Sirri marriages. Therefore, good muslims should not conduct Sirri marriages. The reality whereby many Sirri marriages are still conducted shows the need for legal enforcement through the ratification of the Draft Bill.